Building block design for composite metamaterial with an ultra-low thermal expansion and high-level specific modulus. (15th November 2022) - Yu, Huabin; Wang, Haomiao; Guo, Xiaogang; Liang, Bo; Wang, Xiaoyue; Zhou, Hao; Zhang, Xiaoyu; Chen, Mingji; Lei, Hongshuai
Abstract: The metamaterials with unique thermal expansions are attracting increasing interest in a broad range of applications. Despite numerous metamaterials with unique thermal expansions have been demonstrated, none of them is without inherent laminations, either in terms of their limited design freedom, the immutability feature of the specimen once fabricated, and the low specific modulus. Inspired by the building block (e.g., Lego toys), this paper introduces a generalized design strategy for reconfigurable mechanical metamaterials with unique thermal/mechanical performances. The triangle metamaterial constructed by the specific collection of structural building blocks shows the capability of this design for achieving an unprecedented low effective CTE (i.e., 0.07 ppm/°C), high-level lightweight (i.e., 0.549 g/cm 3 ), and a remarkable relative specific modulus (i.e., 41385.55 kN∙mm/kg). More specifically, the assembly method with well-designed connectors presented here promises the mechanical robustness and reconfigurable feature of metamaterials. Additionally, the thermal–mechanical factor Φ is adopted for accurately characterizing compatibility of thermal deformation and mechanical properties of the metamaterial. Finally, the comparison of the absolute value of CTE and the comprehensive thermal–mechanical property serves a quantitative comparison of the mechanical metamaterials demonstrated here to the previous reported results, indicating the capability of our designs for their practical engineering applications.